Investigating the effects of foreign direct investment inflows on economic growth in Cambodia - VAT, Namon (KDI School, 2022)
Foreign Direct Investment (FDI) is crucial for economic growth and development since it promotes technology and innovation transfers and capital accumulation. The main objectives of this study are to analyze and evaluate Cambodia''s FDI inflows and the impact on the economy, especially the contribution from 1993 to 2019. Using a time-series data regression method, the Vector Autor Regressive (VAR) model, Vector Error Correction (VEC), and co- integration technique analyze the quantitative data. The study confirms the long-run association between foreign direct investment inflows and economic growth. Furthermore, the study carries out the granger causality test among economic growth rate (GDP), Foreign Direct Investment (FDI), Total Labor Force (LF), and Gross Fixed Capital Formation (K). The findings suggest a bidirectional relationship between GDP and FDI in the long run. To be specific, one percent increase in foreign direct investment leads to an 0.09 percent increase in GDP growth.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Investments, Foreign--Cambodia; Economic development--Cambodia